Leituras de professores: uma teoria da prática - Terra, Ernani (2012)
The work Leituras de professores: uma teoria da prática, by Ernani Terra, under orientation of Prof Dr Anna Maria Marques Cintra, presents the results of the research that has investigated reading habits of High-School Portuguese teachers in the São Paulo metropolitan area. The author s aims are to identify what the informants read in their spare time and whether these readings are of free choice. The research follows two hypotheses: a) teachers spare time readings are strongly related to their professional practice; b) Portuguese language teachers autonomy in deciding what they want to read in their spare time is not complete, since it is determined by institutional needs. The author has not found research on spare time reading by teachers in the libraries of three universities in the state of São Paulo. Nor has he found studies which analyze whether they share these readings with the students. This research might bring subsidies to guide the pedagogical action of teachers, especially with relation to reading. The work was based on bibliographical research and on critical review of literature, which served as a basis for the analysis and interpretation of quantitative and qualitative data. The analysis has been bases upon three independent pillars that are related to the general topic of the research: 1. Analysis if the characteristics of free time and leisure activities; 2. Reading profile in Brazil; 3. Analysis of teacher s practices in relation to reading. Our theoretical support is Theodor Adorno, Joffre Dumazedier and Frederic Munné for item 1; Laurence Helleweel, Marisa Lajolo, Regina Zilberman and Magda Soares for item 2; Pierre Bourdieu and Michel de Certeau for item 3. The study reveals our informants readings during the time they are freed from work and domestic chores are linked to their professional practice and to their professional development